The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1108/idd-10-2021-0111
|View full text |Cite
|
Sign up to set email alerts
|

Factors that determine open data readiness among scholars: experience from selected universities in Tanzania

Abstract: Purpose This study aims to investigate the factors determining the readiness for uptake of open data (OD) in Tanzania. Specifically, this study intended to answer the question that sought to find out the factors that influence the implementation of OD in universities under study in a view to aligning with recommended strategies for optimizing the use of data in the open science era. Design/methodology/approach This study used a cross-sectional survey design whereby data were collected using quantitative and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…OS is a relatively new avenue in the research landscape of Tanzania, with reported practices placing a heavy focus on open access (OA) (Dulle et al 2010;Mgonzo & Yonah 2014;Buhomoli & Muneja 2022). OS adoption in Tanzania has been slow despite several initiatives geared towards promoting the movement (Muneja & Ndenje-Sichalwe 2016;Kaijage 2017;Siyao et al 2017;Fossner 2021;Personal communication 2022;TCC Africa 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OS is a relatively new avenue in the research landscape of Tanzania, with reported practices placing a heavy focus on open access (OA) (Dulle et al 2010;Mgonzo & Yonah 2014;Buhomoli & Muneja 2022). OS adoption in Tanzania has been slow despite several initiatives geared towards promoting the movement (Muneja & Ndenje-Sichalwe 2016;Kaijage 2017;Siyao et al 2017;Fossner 2021;Personal communication 2022;TCC Africa 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The slow trend may be due to low awareness of the OS practices among research and academic institutions. Misconceptions and concerns for misuse of data such as loss of patent rights, data theft and manipulation in open repositories may hold back researchers from practising OS (Buhomoli & Muneja 2022). Elsewhere in Africa, a lack of clear institutional policies to guide application of OS principles has also been a hindrance and may be the case for Tanzania as well (Mwelwa et al 2020;Okafor et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Matonkar and Dhuri (2021) investigated how open education and free Internet resources were used in India during the Covid-19 pandemic and discovered that the vast majority of participants were unfamiliar with OER. Further, a study by Buhomoli and Muneja (2022) shows that researchers and decisionmakers have little or no awareness of issues connected to open science, such as open data and OERs. Appiah et al, (2020) conducted a study at Ghana's Kumasi Technical University on an evocative appraisal of OER awareness, attitude, and utilization.…”
Section: Awareness Of Oermentioning
confidence: 99%
“…Other institutions joined the initiative by developing the IRs, such as Mzumbe University IR (MU IR), Sokoine University of Agriculture IR (SUA IR), Muhimbili University of Health and Allied Sciences IR (MUHAS IR), and the University of Dodoma IR (UDOM IR) (Muneja, 2009;Nunda & Elia, 2018). The IR adoption and use in Tanzania have been motivated by several aspects, such as increasing institutional visibility, research outputs, and citation impacts (Buhomoli & Muneja, 2023;Mbughuni et al, 2022;Nunda & Elia, 2018).…”
Section: Introductionmentioning
confidence: 99%